Birkeland currents during substorms: Statistical evidence for intensification of Regions 1 and 2 currents after onset and a localized signature of auroral dimming. Issue 6 (28th June 2017) - Coxon, John C.; Rae, I. Jonathan; Forsyth, Colin; Jackman, Caitriona M.; Fear, Robert C.; Anderson, Brian J.
Abstract: We conduct a superposed epoch analysis of Birkeland current densities from AMPERE (Active Magnetosphere and Planetary Electrodynamics Response Experiment) using isolated substorm expansion phase onsets identified by an independently derived data set. In order to evaluate whether R1 and R2 currents contribute to the substorm current wedge, we rotate global maps of Birkeland currents into a common coordinate system centered on the magnetic local time of substorm onset. When the latitude of substorm is taken into account, it is clear that both R1 and R2 current systems play a role in substorm onset, contrary to previous studies which found that R2 current did not contribute. The latitude of substorm onset is colocated with the interface between R1 and R2 currents, allowing us to infer that R1 current closes just tailward and R2 current closes just earthward of the associated current disruption in the tail. AMPERE is the first data set to give near‐instantaneous measurements of Birkeland current across the whole polar cap, and this study addresses apparent discrepancies in previous studies which have used AMPERE to examine the morphology of the substorm current wedge. Finally, we present evidence for an extremely localized reduction in current density immediately prior to substorm onset, and we interpret this as the first statistical signature of auroral dimming in Birkeland current. Key Points: The latitude of the substorm onset is colocated with the interface between the R1 and R2 systems Both Region 1 (R1) and Region 2 (R2) current densities enhance at substorm onset Upward current density decreases prior to onset in a localized area, consistent with auroral dimming